18F-FDG-PET correlates of ımpulse control disorder in a diabetic patient - Yuluğ, Burak; Hanoğlu, Lütfü; Tavlı, Ahmet Mithat; Çakır, Tansel; Khanmammadov, Elmir; Olmusçelik, Oktay (Bentham Scıence Publ Ltd, 2016)
Background: Studies have already shown that hyperglycemia and insulin resistance are significantly associated with the impairment of cerebral glucose metabolism that may secondary lead to cognitive disturbances. In this study, we aimed to evaluate the neurometabolic correlates of diabetes in a patient with Intermittent explosive disorder (IED). Methods: We have investigated the cerebral glucose metabolism via 2-[18F]-fluoro-2-deoxy-D-glucose positron emission tomography (FDG-PET) in a diabetic patient with aggressive outbursts. Results: We have found significantly reduced glucose uptake in left temporoparietal region, pontin area, and left nucleus lentiformis. Discussion: Our present results indicate decreased cerebral glucose metabolism in specific cerebral cortical and subcortical areas. The main limitation of this report is that, this is a single case study and that these findings need to be replicated in well-conducted randomized controlled studies by using additional neuroquantitative methods.
WOS: 000397116200009
PubMed ID: 27697074
Keywords: Diabetes Mellitus; FDG-PET; Impulse Control Disorder